Demonstrating advanced practice provider value: Implementing a new advanced practice provider billing algorithm. Issue 2 (February 2019) - Brooks, Paula B.; Fulton, Megan E.
ABSTRACT: Background: Rapid changes in healthcare are driving the adjustment of work flow by which providers serve patients in team-based care. Specifically, there is a need to develop more effective and efficient utilization with accurate attribution of advanced practice providers' (APPs) productivity. Local problem: The directors of the APP-Best Practice Center conducted assessments of each clinical area at the Medical University of South Carolina (MUSC) Health, a large academic medical center. A knowledge gap was identified, not only regarding billing practices of the APPs (NPs and physician assistants) but also in the use of APPs to practice to the fullest extent of their license, education, and experience. Methods: By substantiating APPs' contribution margin through the process of implementing a new standardized APP billing algorithm, a change in practice was accepted by senior leadership and a new APP billing algorithm was built that follows updated practice laws, compliance/legal standards, and hospital bylaws and regulations. Interventions: A new billing algorithm was implemented on July 1, 2017, and outcomes were evaluated 12 months after implementation. Results: This project uncovered the work already performed by APPs while increasing relative value units, collections, and overall patient encounters by the APP/physician team. Findings suggest improved utilization and appropriate attribution of productivity. Conclusions: With the APP workforce growing, the implementation of electronic medical record systems, and today's healthcare financial constraints, healthcare systems must standardize their billing practices. The APP billing algorithm is a critical tool that will help to meet this demand.